Development of a Framework for Risk-Based Integrated Safety Audit to Enhance Construction Safety Performance - Danang B. Nugroho; Yusuf Latief; Mochamad A. Wibowo; Rosmariani Arifuddin; Fatma Lestari; Muhammad N. Akram (Salehan Institute of Higher Education, 2024)
Presently, there is a notable surge in infrastructure development, leading to a heightened occurrence of accidents within the construction sector. This trend has positioned the construction industry as one of the most accident-prone areas compared to other sectors. This suggests that the current construction safety audit procedures have not proven effective in preventing accidents. Typically, audits are conducted primarily during the construction phase, with infrequent assessments during the design phase. According to the Szymberski theory, actions taken during the design phase significantly influence the occurrence of accidents more than those taken during construction. Previous research has discussed a lot about safety management systems. However, it has not discussed how to assure the quality of its implementation. Considering this, the research aims to (a) identify the processes, elements, activities, sub-elements, objectives, criteria, and risks associated with construction safety audits and (b) formulate an integrated, risk-based audit process covering both the design and construction phases. This qualitative research employed the Delphi method to gather insights from construction safety experts, and the developed audit process utilized a risk management approach. The resulting audit process integrates principles from ISO 19011:2018 and Regulation of the Minister of Public Works and Housing Number 10 of 2021. The findings revealed 34 activities in audit program management, 34 activities in audit implementation, and 32 sub-elements in audit criteria. These components are incorporated into a comprehensive construction safety audit framework, organizing audit processes, activities, and criteria. This framework underscores that improving construction safety performance is not solely confined to the construction phase but extends to the design phase as well. The audit results serve as a foundation for continuous improvement, aiding in enhancing safety performance and preventing accidents within the construction industry. Doi: 10.28991/CEJ-2024-010-03-08 Full Text: PDF